Reducing the development gaps between regions in Poland with the use of European Union funds - Czudec, Adam; Kata, Ryszard; Wosiek, Małgorzata (Technological and Economic Development of Economy, 2019)
The paper evaluates the processes of regional income convergence in Poland. This new research approach involves an attempt to assess the process of convergence from the point of view of development gaps. Six key development gaps were considered in the region of Eastern Poland, which is a singular case, significantly different from other regions. A dynamic panel data model was applied to investigate the impact of EU funds on the progress made towards closing these development gaps. Among the analysed development gaps, only the structural gap was not reduced in the period 2004–2015. Studies have also revealed the different impact of structural funds on each category of development gaps (a positive impact on reducing the regional transport accessibility gap and the investment gap, but negative – on reducing the innovation gap). Research has suggested the need for a change in the structure of using EU funds in the period 2014–2020 to favour stronger support for entrepreneurship and the creation of new jobs. Greater stimulation of the economic structure of peripheral regions has been proposed as the prerequisite for the future reduction in the discrepancies between regions and for the intensification of convergence. First published online 2 April 2019